A simple role for BDNF in learning and memory? - Cunha, Carla; Brambilla, Riccardo; Thomas, Kerrie L. (Frontiers in Molecular Neuroscience, 2010)
Since its discovery almost three decades ago, the secreted neurotrophin brain-derived neurotrophic factor (BDNF) has been firmly implicated in the differentiation and survival of neurons of the CNS. More recently, BDNF has also emerged as an important regulator of synaptogenesis and synaptic plasticity mechanisms underlying learning and memory in the adult CNS. In this review we will discuss our knowledge about the multiple intracellular signalling pathways activated by BDNF, and the role of this neurotrophin in long-term synaptic plasticity and memory formation as well as in synaptogenesis. We will show that maturation of BDNF, its cellular localisation and its ability to regulate both excitatory and inhibitory synapses in the CNS may result in conflicting alterations in synaptic plasticity and memory formation. Lack of a precise knowledge about the mechanisms by which BDNF influences higher cognitive functions and complex behaviours may constitute a severe limitation in the possibility to devise BDNF-based therapeutics for human disorders of the CNS.